Caffeine combination chemotherapy for oral squamous cell carcinoma - Aoki, Takayuki; Yamazaki, Hiroshi; Kaneko, Akihiro; Tsukinoki, Keiichi; Sasaki, Jiro; Ohta, Yoshihide; Watanabe, Daisuke; Karakida, Kazunari (Japanese Journal of Chemotherapy, 2001)
Caffeine is known of inhibit DNA repair of cancer cells. The anticancer effects of caffeine increase when it is used in combination with anticarcinogenic agents. We examined the clinical and side effects of treating oral squamous cell carcinoma with intravenous (IV) drips of cisplatin (CDDP), etoposide (VP-16), bleomycin hydrochloride (BLM), and caffeine as a neoadjuvant. CDDP (25mg) was infused by IV for 2 hours, VP-16 (100mg) 1 hour, and BLM (20mg) 16 hours. Caffeine (1, 000mg) was them infused by IV for 18 hours. Subjects were 17 patients with oral squamous cell carcinoma, of these 14 underwent post treatment surgery, and cancer regression was seen in 8 of the 14 (57%). Side effects in the 17 patients were appetite loss (53%), leukopenia (47%), and nausea (29%). Insomnia did not occur. Other side effects were fever (2 cases), paleness (1 case), lip erosion (1 case) and skin eruption (1 case). This regimen has proven useful in treatment, but further work is necessary to determine the most efficacious doses.